Tagetes Patula y T Erecta para Controlar Meloidogyne Incognita y Hellcotylenchus Dihystera - Vergel German; Sierra Guillermo; Volcy Charles (Revista Facultad Nacional de Agronomía Medellín, 1979)
An experiment was carried out under greenhouse conditions to test the control of Meloidogyne incognita and Helicotylenchus dihystera by Tagetes patula nana var. Petit Harmony and T. erecta var. Orange.
For each of these nematode species, the population levels tested were considered as high, moderate and low. These populations were obtained mixing infested soil with sterilized one.
Both Tagetes species gave satisfactory control. The decrease in population of nematodes in comparison with tomato was ranged from 15.5 to 136.3% depencing on the nematode species and on its population level on the soil No significate difference was found between the two Tagetes species.
There was a greater decrease in population density for M. incognita than for
H. dihystera; this was particulary true at the lowest population levels tested. In the case of M. incognita, an inverse relation was found between degree of control and population density of these nematodes in soil.